Efficiency Analysis of Izmir Metro in Its Current State - Selvi, Ömer; Selvi, Ömer; Gür, Nazim Güneş (Izmir Institute of Technology, 2002)
This thesis analyzes the efficiency of the current state of İzmir Metro System by using the Method of Comparative Benchmarking. In the theoretical framework, the need and emerge of each transit mode is discussed, and the importance of mass transit concept is pointed out. The development of urban transit and the need for metro systems are examined. The characteristics of the prevailing mass transit systems modes are described and compared. Efficiency concept, as the quality of well and effective service, without wasting time, money, or energy, is analyzed. Different approaches to efficiency are described. In the view of efficiency; right mode choice, right travel demand estimation, right choice of routes and stations are discussed and efficiency criteria for public transport are determined. The Method of Comparative Benchmarking Analysis is examined for the measurement of efficiency. Applications and the uses of this method in public transportation and in metro systems are evaluated. Specifically, performance measurement stages of that performance increaser method are employed to measure the performance of İzmir Metro. İzmir Metro is analyzed and then compared with similar systems worldwide. Key Words: İzmir Metro, Efficiency, Urban Mass Transit, Comparative Benchmarking Analysis
Thesis (Master)--Izmir Institute of Technology, City and Regional Planning, Izmir, 2002
Includes bibliographical references (leaves: 83-87)
Text in English; Abstract: Turkish and English
viii, 87 leaves
Keywords: HT390. S45 2002; Urban transportation; Urban transportation--Planning; Subways--Turkey--Izmir